1993
DOI: 10.1007/bf00187453
|View full text |Cite
|
Sign up to set email alerts
|

Primate ABO glycosyltransferases: Evidence for trans-species evolution

Abstract: The human ABO blood group system is controlled by alleles at a single locus on chromosome 9. The alleles encode glycosyltransferases, which add different sugar residues to the terminal part of the oligosaccharide core, thus generating the A or B antigens; an allele encoding enzymatically inactive protein is responsible for the blood group O. The A and B antigens are present not only in humans, but also in many other primate species and it has been proposed that the AB polymorphism was established long before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 17 publications
(11 reference statements)
5
33
1
2
Order By: Relevance
“…The glycosyltransferases responsible for A or B phenotypes in primates were shown to conserve amino acid substitutions corresponding to codons 266 and 268 in humans. A similar study was also reported by others (18). Through comparative sequence analyses of the ABO genes from humans and apes, we and others proposed a convergent hypothesis of evolution that ABO genes arose from independent mutations after the speciation of humans and apes (19,20).…”
supporting
confidence: 88%
“…The glycosyltransferases responsible for A or B phenotypes in primates were shown to conserve amino acid substitutions corresponding to codons 266 and 268 in humans. A similar study was also reported by others (18). Through comparative sequence analyses of the ABO genes from humans and apes, we and others proposed a convergent hypothesis of evolution that ABO genes arose from independent mutations after the speciation of humans and apes (19,20).…”
supporting
confidence: 88%
“…invokes parallel evolution as an explanation for the interspecific sharing of antigenic determinants. The former hypothesis was supported by Martinko et al (1993); the latter was proposed by Saitou and Yamamoto (1997) and is more consistent with partial intron 6 hominoid sequence data described by O'hUigin et al (1997). In Old World monkey, we should consider these two hypotheses.…”
Section: Resultssupporting
confidence: 67%
“…Kominato et al (1992) determined the ABO group gene exon 7 sequences of chimpanzee, gorilla, orangutan, crabeating macaque, and yellow baboon. Martinko et al (1993) supported the trans-species polymorphism hypothesis in hominoids based on their sequence data. Saitou and Yamamoto (1997) analyzed sequence data of the ABO blood group gene exon 7 that determines the activity of the glycosyltransferase-encoding genes from the human, chimpanzee, gorilla, orangutan, and some Old World monkeys.…”
Section: Introductionsupporting
confidence: 63%
“…The initial suggestion of long-term balancing selection came from the fact that the AB antigen-antibody phenotype is present in many primates, including some New World monkeys (Blancher et al 2000). Furthermore, it has been shown biochemically that only two nucleotides, separated by 6 bp, differentiate the A allele from the B allele (Yamamoto and Hakomori 1990) and that these two nucleotides demonstrate apparent transspecies polymorphism within humans, chimpanzees, and gorillas (Martinko et al 1993). In contrast, the O allele appears to have arisen multiple times in humans but is rare in nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%